Leaf morphology and leaf chemical composition in three Quercus (Fagaceae) species along a rainfall gradient in NE Spain - Castro-Diez, P (Trees-Structure and …, 1997)
mLeaf features were examined in three Quercus species (Q. coccifera, Q. ilex and Q. faginea) along a steep rainfall gradient in NE Spain. The analyzed leaf traits were area, thickness, density, specific mass, leaf concentration of nitrogen, phosphorous, lignin, cellulose and hemicellulose, both on a dry weight basis (Nw, Pw, Lw, Cw, Hw) and on an area basis (Na, Pa, La, Ca, Ha). These traits were regressed against annual precipitation and correlated with each other, revealing different response patterns in the three species. Q. faginea, a deciduous tree, did not show any significant correlation with rainfall. In Q. coccifera, an evergreen shrub, Nw, Na, Lw, La and Ca increased with higher annual rainfall, while Hw decreased. In Q. ilex, an evergreen tree, leaf area, Pw and Lw increased with precipitation, whereas specific leaf mass, thickness and Ha showed the reverse response. Correlations between the leaf features revealed that specific mass variation in Q. faginea and Q. coccifera could be explained by changes in leaf density, while in Q. ilex specific leaf mass was correlated with thickness. Specific leaf mass in the three species appeared positively correlated with all the chemical components on a leaf area basis except with lignin in Q. ilex and with P in Q. ilex and Q. faginea. In these two tree species Pw showed a negative correlation with specific leaf mass. It is suggested that each species has a different mechanism to cope with water shortage which is to a great extent related to its structure as a whole, and to its habit.
Keywords: environmental gradient; Leaf fibre content; leaf morphology; Leaf nutrient content; Mediterranean climate